2020
DOI: 10.3390/molecules25092167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solvents on Fe–Lignin Precursors for Production Graphene-Based Nanostructures

Abstract: Kraft lignin was catalytically graphitized to graphene-based nanostructures at high temperature under non-oxidative atmospheres. To obtain the best catalytic performance, a uniform catalyst–lignin mixture must be made by bonding transitional metal (M) ions to oxygen (O), sulfur (S) or nitrogen (N)-containing functional groups in kraft lignin. One of the strategies is to dissolve or disperse kraft lignin in a suitable solvent, whereby the polymer chains in the condensed lignin molecules will be detangled and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
(81 reference statements)
1
7
0
Order By: Relevance
“…The phase state of iron species was mainly γ-Fe 2 O 3 , only containing a small amount of χ-Fe 5 C 2 ; the carbonization degree of these two catalysts was extremely low. Yan 59 and Lü6 0 found that Fe with a smaller particle size was much easier to be reduced and carbonized during the Fischer−Tropsch reaction. Combined with the previous results of electronic properties and iron particle sizes, it could be inferred that for FeNa/EG-O, although it contained a small amount of N doping and was relatively easy to be reduced compared with FeNa/EG-C, it was difficult to be carbonized during the reaction process due to its large particle size of iron.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The phase state of iron species was mainly γ-Fe 2 O 3 , only containing a small amount of χ-Fe 5 C 2 ; the carbonization degree of these two catalysts was extremely low. Yan 59 and Lü6 0 found that Fe with a smaller particle size was much easier to be reduced and carbonized during the Fischer−Tropsch reaction. Combined with the previous results of electronic properties and iron particle sizes, it could be inferred that for FeNa/EG-O, although it contained a small amount of N doping and was relatively easy to be reduced compared with FeNa/EG-C, it was difficult to be carbonized during the reaction process due to its large particle size of iron.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the Fe-lignin composites, iron ions were uniformly distributed throughout lignin molecules by chelating to the oxygen-containing functional groups [ 37 ]. These Fe-lignin composites are thermally unstable and are decomposed to lignin char embedded with nano iron oxide particles when heated at 200–300 °C [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the Fe-lignin composites, iron ions were uniformly distributed throughout lignin molecules by chelating to the oxygen-containing functional groups [ 37 ]. These Fe-lignin composites are thermally unstable and are decomposed to lignin char embedded with nano iron oxide particles when heated at 200–300 °C [ 37 , 38 ]. At elevated temperatures, the lignin char was catalytically carbonized, and alien elements, oxygen, and hydrogen in the lignin char were eliminated as gaseous water, carbon monoxide, carbon dioxide, and hydrogen ( Figure 1 a).…”
Section: Resultsmentioning
confidence: 99%
“…Mostly the fine fibers were obtained by this concentration up to 2m diameter size. The peak of wave length of 1100 cm -1 , corresponding to C-O stretching conjugate (lignin) and 1321 cm -1 , ring condensed stretching (lignin) revealed the removal of excess lignin from enset fibers [32]. Moreover, there was a clear peak shape difference between untreated and treated enset fiber at wave number of 1100cm 1 .…”
Section: Chemical Analysis Of the Neat And Treated Enset Fibers With Ftir Spectroscopymentioning
confidence: 96%